High-Yield Blood-Centric Logistics for Locking-In GWOT and Ukraine Medical Lessons: Ready for Tomorrow’s Large-Scale Combat Operations - Randy Michael; Conner Smith; Sara Hey; Rosalyn Clemente-Fuentes (Journal of Operational Medicine, 2026)
Hemorrhagic shock remains the leading cause of preventable death in combat trauma, particularly before casualties reach definitive surgical care, making blood-centric damage control resuscitation a critical priority for future large-scale combat operations. This manuscript synthesizes lessons from the Global War on Terror, Ukraine, and allied military experience to argue that low-titer group O whole blood must be treated as a mission-essential capability in forward and austere environments, but its effectiveness depends on reliable cold-chain storage, active blood warming, calcium replacement, trained personnel, and standardized protocols. Failure of any link in this system can lead to product wastage, delayed transfusion, hypothermia, coagulopathy, acidosis, hypocalcemia, and, ultimately, increased mortality. Recent conflicts further demonstrate that centralized medical infrastructure and evacuation-dependent models are vulnerable to disruption, requiring decentralized, mobile, and technologically adaptive blood logistics such as forward storage, compact refrigeration and warming devices, micro-hospitals, and unmanned delivery platforms. Preparing for tomorrow’s combat casualty care environment requires a resilient blood-centric logistics paradigm that ensures lifesaving blood products are available at or near the point of injury whenever and wherever they are needed.